Low‐cost dye‐sensitized solar cells with ball‐milled tellurium‐doped graphene as counter electrodes and a natural sensitizer dye. (20th June 2019) - Alami, Abdul Hai; Aokal, Kamilia; Zhang, Di; Taieb, Aya; Faraj, Mohammed; Alhammadi, Alya; Ashraf, Juveiriah Mohammed; Soudan, Bassel; El Hajjar, Jinan; Irimia‐Vladu, Mihai
Summary: This paper presents a facile and economic development of dye‐sensitized solar cells using a nonprecious counter electrode made from ball‐milled tellurium‐doped graphene (Te‐Gr) and a natural sensitizer extracted from Calotropis gigantea leaves. The prepared materials were characterized using various techniques, such as Raman spectroscopy, X‐ray diffraction (XRD), atomic force microscopy (AFM), impedance spectroscopy, and scanning electron microscopy with built‐in energy‐dispersive X‐ray spectroscopy (SEM with EDS). The electrochemical activity of the produced counter electrodes and the impedance of the fabricated cells were examined and discussed to devise plans for future enhancement of cell performance. A clear pattern of improvement was found when using cost‐effective Te‐Gr relative to the costly platinum counter electrodes, especially when compared with cells employing another natural sensitizer. The results show approximately 51% enhancement over chlorophyll‐based cells made from spinach, where the added advantage in our approach is the utilization of an abundant plant extract with little nutritional appeal.